Determinan Perilaku Impulsive Buying pada Mahasiswa Penerima Kip-K dalam Perspektif Ekonomi Syariah - Rahmat Hidayatulloh; Listian Indriyani Achmad; Sukron Mamun; Yudianto Achmad (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to examine the effect of Living Cost Assistance and Peer Conformity on Impulsive Buying behavior among KIP-K scholarship recipients in the Sharia Economics Study Program at Universitas Pelita Bangsa, within the perspective of Islamic economics. This research employed a quantitative approach using a survey method through questionnaires distributed to 65 respondents selected using the Slovin formula. Data were analyzed using multiple linear regression with SPSS. The results indicate that Living Cost Assistance has a positive and significant effect on Impulsive Buying (t = 3.031; p = 0.004), and Peer Conformity also has a positive and significant effect (t = 13.699; p = 0.000). Simultaneously, both variables significantly influence Impulsive Buying (F = 111.631; p = 0.000), with a coefficient of determination (R²) of 0.783. From the perspective of Islamic economics, these findings suggest that financial availability and social pressure may encourage consumption beyond essential needs if not accompanied by self-control and prudent financial management. Therefore, strengthening financial literacy based on the principles of tawazun (balance), qana’ah (contentment), and mas’uliyah (responsibility) is essential in managing living cost assistance.